The Battle of Stalingrad in the focus of western historiography - A. A. Paderin (Vestnik MGIMO-Universiteta)
This article is about: The Battle of Stalingrad is drastic turning point in World War II. The Battle of Stalingrad is discussed by western historians in markedly different ways. Methods and techniques of perversion the historical significance of the Battle of Stalingrad. Different ways to expose misrepresentation of crucial events and results of the Battle of Stalingrad.